THE EFFECT OF SILENT WAY METHOD ON THE STUDENTS’ SPEAKING COMPETENCE AT THE TENTH GRADE OF SMAN 1 KONTUKOOWUNA - Sani, Wa; Rohmana, Rohmana; Muhsin, Muhammad Khusnun (Universitas Halu Oleo, 2020)
The objective of the study was to find out whether or not the silent way method can significantly affect students’ speaking competence. The design of this study was a pre-experimental research design (one group pre-test post-test design). The researcher applied a simple random sampling technique. The class 10 IPA1 was taken as the sample of the study with 18 students. The instrument of this study was an oral test in pre-test and post-test. This research was conducted through the following procedures: giving a pre-test, applying treatments and giving a post-test. The data were analyzed by using paired sample t-test. Through the SPSS16.0 version. The result showed that the mean score on students’ speaking competence in a pre-test was 32.22 and in the post-test was 49.44. Hypothesis testing found that the value of sig (2 tailed) was 0.00 while the significant alpha value was 0.0. It could be concluded that the value of sig (2 tailed) was lower than the significant alpha value was (0.00<0.05). Therefore, H1 was accepted and H0 was rejected. So, the use of the silent way method had a significant on the students’ speaking competence at the tenth grade of SMAN 1 Kontu kowuna.